The Arbitration Clause as Super Contract - Richard Frankel (Washington University Law Review, 2014)
It is widely acknowledged that the purpose of the Federal Arbitration Act (FAA) was to place arbitration clauses on equal footing with other contracts. Nonetheless, federal and state courts have turned arbitration clauses into “super contracts” by creating special interpretive rules for arbitration clauses that do not apply to other contracts. In doing so, they have relied extensively, and incorrectly, on the Supreme Court’s determination that the FAA embodies a federal policy favoring arbitration. While many scholars have focused attention on the public policy rationales for and against arbitration, few have explored how arbitration clauses should be interpreted. This Article fills that gap and asserts that the judiciary’s inappropriate reliance on the federal policy favoring arbitration distorts state contract law to push cases into arbitration that do not belong there, thereby unfairly depriving litigants of access to the courts. By creating special rules that favor arbitration and that deviate from state contract law, courts are enforcing arbitration agreements in situations where they would not enforce other agreements. This Article challenges the judiciary’s favored treatment of arbitration clauses and identifies several areas in which arbitration clauses are being over‑enforced as a result. The fact that courts send too many disputes into arbitration also is significant because it undermines the perception, common among both academics and judges, that courts remain hostile to arbitration rather than supportive of it. Because the original purpose of the Federal Arbitration Act was to make arbitration clauses just like other contracts, this Article proposes that courts should construe the federal policy favoring arbitration in a way that is consistent with state contract law rather than in a way that uproots it. Doing so best ensures that litigants are not unfairly forced into arbitration where they never agreed to it.
Keywords: Federal Arbitration Act; FAA; Moses H. Cone